Cooperação para inovar: uma análise qualitativa da interação entre cooperativas de crédito e startups - Cunha, Plinio Regis Moraes da (Universidade do Vale do Rio dos Sinos, 2021)
Innovation is a recurring theme in academic research and in the business world, having been related to the development of new services, business models and management practices. Consequently, companies have sought to expand their innovative capacity, making the concept of open innovation a new paradigm for the organization of this theme. In recent years, the growing viability of startups, mainly due to their ability to innovate, has motivated corporations to collaborate with startups to transform them into drivers of corporate innovation. In this context, cooperatives have been looking for ways to increase their efficiency and effectiveness, aiming to increase the satisfaction of the needs of their members, so they have been looking for innovations that make this possible through collaboration with startups. This dissertation evaluated, in a dyadic context, the connections between credit unions and startups, simultaneously collecting the perspectives of cooperatives and startups. Using the method of comparative qualitative analysis (QCA), this study compared 20 interviews, investigating the background, mechanisms, and results of partnerships between credit unions and startups. The analyzes showed that the five constructs studied have a certain degree of impact to generate innovation, which are presented in the results discussion chapter. In this context, this study contributed to the diversification of scientific research by cooperatives, open innovation, and startups in Brazil.
Keywords: Inovação; Inovação aberta; Cooperativa; Cooperativa de crédito; Startup; Análise qualitativa comparativa (QCA); Innovation; Open innovation; Cooperative; Credit union; Qualitative comparative analysis (QCA); ACCNPQ::Ciências Sociais Aplicadas::Administração